Medici și pacienți – două perspective asupra reformei și descentralizării din sistemul sanitar - Popa, Adela Elena (Calitatea Vieții, 2011)
The health care reform, and the decentralization of the health system are perceived, understood and accepted in different ways, by the different social actors involved. This paper takes a close look to these two processes that Romania underwent in the last years, from two perspectives: the human resources in the medical system (physicians) and the system’s beneficiaries (patients). Two levels of analysis are pursued, with a quantitative approach (secondary analysis on Opinion barometer of Health Care Services, considering data between 2002 and 2008). The longitudinal analysis is focused on very recent changes in Romanian health system, initiated by the hospitals decentralization process announced since 2009, started in June 2010 and completed by the end of 2010. All these changes are analysed in the broader context of health care reform.